KEKERASAN DAN KRIMINALITAS DI PERKOTAAN: ANOMALI KOTA MAKASSAR MODERN PADA ABAD KE-20 - Ilham Ilham (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
Throughout the 20th century, Makassar city continued to practice the ideas of modernity both in its physical development of the city and in its social and cultural life. In this context, urban problems developed both environmentally and socially. Some prominent aspects were violence and crime which grew more complex over time. Violence appeared in discriminatory attitudes in the space management and use. If in the colonial period, discriminatory attitudes were based on nationality and skin color, in the independence era, discriminatory attitudes most felt by residents who did not have access to the power. Modernization of the city seems to overlook comprehensive and sustainable improvement of urban kampungs. In the long-term environmental damages such as floods, fires, and infectious diseases occurred. Weak enforcement to control the practice of prostitution and gambling also caused violence and criminal acts. Other forms of crime such as theft, fighting, murder, robbery, inter-kampung war or juvenile delinquency occurred in all parts of the city, both during the day and at night. Various forms of violence and crime are anomalies of the ideals of a modern city. In certain conditions, violence and crime created as an accumulation of "disappointment" of the modernization project. This condition created alienation or displacement of individuals in the culture of modern (city). It occurred because there was widespread “inequality” in various forms, such as injustice, helplessness or inability to face (transformation in) the new age. These modern Makassar city anomalies are like irony experienced in urban spaces, villages, and people's lives.   Keywords: Anomalies, Crime, Modern Makassar City, Violence, 20th Century “